Factors Associated with High-Quality Cardiopulmonary Resuscitation Performed by Bystander - Hye Ji Park; Won Jung Jeong; Hyung Jun Moon; Gi Woon Kim; Jin Seong Cho; Kyoung Mi Lee; Hyuk Joong Choi; Yong Jin Park; Choung Ah Lee (Emergency Medicine International)
Bystander cardiopulmonary dresuscitation (CPR) improves the survival and neurological outcomes of sudden cardiac arrest patients. The rate of bystander CPR is increasing; however, its performance quality has not been evaluated in detail. In this study, emergency medical technicians (EMTs) in the field evaluated bystander CPR quality, and we aimed to investigate the association between bystander information and CPR quality. This retrospective cohort study was based on data included in the Smart Advanced Life Support (SALS) registry between January 2016 and December 2017. We included patients older than 18 years who experienced an out-of-hospital cardiac arrest (OHCA) due to medical causes. Bystander CPR quality was judged to be “high” when the hand positions were appropriate and when compression rates of at least 100/min and compression depths of at least 5 cm were achieved. Among 6,769 eligible patients, 3,799 (58.7%) received bystander CPR, and 6% of bystanders performed high-quality CPR. After adjustment, the occurrence of cardiac arrest at home (adjusted odds ratio (aOR), 95% confidence interval (CI); 0.42, 0.27–0.64), witnessed cardiac arrest (1.45, 1.03–2.06), and younger bystander age all showed associations with one another. High-quality CPR led to a 4.29-fold increase in the chance of neurological recovery. In particular, high-quality CPR in patients aged 60 years showed a significant association compared with other age groups (7.61, 1.41–41.04). The main factor affecting CPR quality in this study was the age of the bystander, and older bystanders found it more difficult to maintain CPR quality. To improve the quality of bystander CPR, training among older bystanders should be the focus.